2019
DOI: 10.1016/j.heliyon.2019.e02765
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of green synthesized α-Fe2O3 nanoparticles using Sida cordifolia plant extract

Abstract: The aim of the work is to synthesize iron oxide (α-Fe2O3) nanoparticles using Sida cordifolia plant extract along with evaluation of its antibacterial activity. The presence of phytochemicals in Sida cordifolia methanolic plant extract was investigated by HPTLC and LC-MS/TOF. The probable mechanism for formation of α-Fe2O3 nanoparticles in mediation with plant extract was demonstrated. The green synthesized iron oxide nanoparticles (α-Fe2O3 NPs) were characterized by using X-ray diffraction, scanning, and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 22 publications
(25 reference statements)
4
29
0
1
Order By: Relevance
“…The novel antibacterial activity of Fe 2 O 3 was also recently verified on different works [ 6 , 7 , 45 ]. Pallela et al [ 7 ] synthesized Fe 2 O 3 with an average particle size of 16 nm. The morphological study using SEM images showed the presence of spherical nanoclusters.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The novel antibacterial activity of Fe 2 O 3 was also recently verified on different works [ 6 , 7 , 45 ]. Pallela et al [ 7 ] synthesized Fe 2 O 3 with an average particle size of 16 nm. The morphological study using SEM images showed the presence of spherical nanoclusters.…”
Section: Introductionmentioning
confidence: 68%
“…3881) and K. pneumoniae(KCTC No. 2246) Zn(AC) 2 .2H 2 O ZnO NPs (0001): 60 nm × 10 nm spherical ZnO NAs: 10 nm Conventional NPS: 30 nm [ 16 ] Ultrasonication and milling E. coli (DH5 α ) Commercial ZnO ZnO nanofluid [ 17 ] Nucleation-controlled growth E. coli and S. aureus ZnCl 2 FeCl 2 ·4H 2 O Cubic FCC structure [ 32 ] E. coli (DH5 α ) Commercial ZnO Polyethylene Glycol and Polyvinylpyrolidone ZnO nanofluid [ 39 ] S. aureus KCCM-11335 and E. coli – DH5α ZnO NPs Didodecyldimethyl-ammoniumbromide Flake-like E. coli > S. aureus and [ 40 ] In situ solution casting E. coli and S. aureus Zn(NO 3 ) 2 .6H 2 O oil palm empty fruit bunches ZnO dispersed on cellulose matrix [ 42 ] Green method B subtilis (NCIM 2063), S. aureus (NCIM 2079), E. coli (2065), K. pneumonia (NCIM 2327) Fe(NO 3 ) 3 .9H 2 O 16-nm-sized spherical Fe 2 O 3 with 0.27 nm d value with (104) planes 16 on B. subtilis [ 7 ] Green S. aureus, P. aeruginosa, E. coli and Bacillus subitilis FeCl 3 and Rhus punjabensis ~ 4-nm-sized spherical NPs 10 on P. aeruginosa [ 45 ] Green S. aureus and E. coli Zn(NO 3 ...…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Considering unique properties, they are widely explored for their variety of potential therapeutic applications like antibacterial, antioxidant, anticancer, wound-healing agents, imaging and targeted drug delivery. [9][10][11][12][13] Natural plant sources are gaining vast attention, which can be effectively employed in the preparation of MNPs owing to their easier availability, less toxic behavior and cost-effectiveness. 14,15 The synthesis of MNPs conjugated to various plants such as Cladophora fascicularis, 16 Pinus pinaster, 17 Aerva lanata, 18 Artemisia annua, 19 Hippophae rhamnoides Linn, 20 Eucommia ulmoides, 21 black tea leaf, 22 Averrhoa bilimbi, 23 Salicornia brachiata, 24 Abelmoschus esculentus L, 25 olive leaf, 26 Ipomoea carnea, 27 geranium, 28 and Cissus arnotiana 29 have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, plant-mediated green synthesis of nanoparticles has attracted much attention due to cost effective, environmentally friendly alternative to chemical and physical methods. There are successful reports for plantmediated synthesis of Fe 3 O 4 NPs using various plant extracts such as seed extract of Grape proanthocyanidin [17], leaf extract of Tridaxprocumbens [18], Orange Peel Extract [19], Sidacordifolia plant extract [20], leaves extract of FraxinuschinensisRoxb [21], and Banana Leaves [22]. However, no literature reports are available for the synthesis of Fe 3 O 4 NPs using aqueous leaves extract of Myrtuscommunis L. (MCL),.…”
Section: Numerous Methods Have Been Reported For Synthesis Of Fe 3 Omentioning
confidence: 99%